2015
DOI: 10.21273/hortsci.50.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Pitahaya Accessions Based on Amplified Fragment Length Polymorphism Analysis

Abstract: Hylocereus (Berger) Britton and Rose and Selenicereus (Berger) Britton and Rose are two genera of vine cacti, commonly named pitahaya, that produce fruit that are gaining in popularity as an exotic fruit in many countries. There has also been an increasing interest in these fruits because they can be grown in areas that are prone to drought and heat where other fruit production is not possible. However, there is significant taxonomic confusion regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…Range of number of polymorphic bands (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and % polymorphism (20-92.8%) obtained in this study was almost comparable with results of Tao et al 61 who obtained as 1-7 and 25-100%, respectively, on 50 red and white pulped dragon fruit accessions in China. Like this, the other PCR based marker systems such as RAPD (Legaria Solano et al 62 in Mexico; Junqueira et al 63 in Brazil; Rifat et al 64 in Bangladesh) and AFLP (Pagliaccia et al 65 in USA) markers were also showed high amount of % polymorphism on dragon fruit accessions grown in different regions of world. Comparable PIC value of ISSR markers (0.49-0.92) reported by Tao et al 61 as in our study (0.42-0.91).…”
Section: Discussionmentioning
confidence: 79%
“…Range of number of polymorphic bands (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and % polymorphism (20-92.8%) obtained in this study was almost comparable with results of Tao et al 61 who obtained as 1-7 and 25-100%, respectively, on 50 red and white pulped dragon fruit accessions in China. Like this, the other PCR based marker systems such as RAPD (Legaria Solano et al 62 in Mexico; Junqueira et al 63 in Brazil; Rifat et al 64 in Bangladesh) and AFLP (Pagliaccia et al 65 in USA) markers were also showed high amount of % polymorphism on dragon fruit accessions grown in different regions of world. Comparable PIC value of ISSR markers (0.49-0.92) reported by Tao et al 61 as in our study (0.42-0.91).…”
Section: Discussionmentioning
confidence: 79%
“…These Hylocereus species bear medium to large (200–800 g) edible fruits with broad scales, various peel and flesh colors, and numerous small soft seeds (Tel-Zur et al, 2004a , 2011b ). Among these species, those cultivated worldwide include: the diploids H. undatus and H. monacanthus , which have white, purple or red flesh and a red peel; the tetraploid H. megalanthus , with white flesh and a yellow spiny peel (Lichtenzveig et al, 2000 ); and the spontaneous (natural) or induced (artificial) interspecific hybrids of these three species (Tel-Zur et al, 2012a ; Pagliaccia et al, 2015 ). Interest in these species has increased markedly in recent years, since they are regarded as exotic fruit crops with high economic potential and as a rich source of natural micronutrients (Wu et al, 2006 ) and phytochemicals with therapeutic activities (Song et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a long-term breeding program was begun some three decades ago at Ben-Gurion University of the Negev (BGU) to develop improved hybrids with superior fruit quality, good yields, and enhanced tolerance to extreme temperatures (Tel-Zur, 2013 ). However, this breeding program—like many breeding programs for other minor crops—has been hampered by a variety of factors, including difficulties in applying molecular and other updated breeding approaches, the limited genomic information currently available, and the plants' large genome size and high heterozygosity (Cisneros and Tel-Zur, 2013 ; Plume et al, 2013 ; Pagliaccia et al, 2015 ). In addition to all these factors, 6–10 generations of self-pollination are needed to obtain phenotypically stable homozygote lines.…”
Section: Introductionmentioning
confidence: 99%
“…DNA marker analyses are effective to assess such genetic backgrounds. To date, several types of DNA markers have been utilized to assess the genetic diversity of pitaya, including random-amplified polymorphic DNA (RAPD) (Tel-Zur et al, 2004), inter simple sequence repeats (ISSRs) (Tao et al, 2014), amplified fragment length polymorphism (AFLP) (Pagliaccia et al, 2015), and simple sequence repeats (SSRs) (Pan et al, 2017). Among these DNA markers, SSR markers have several advantages due to high levels of polymorphism, multiple alleles, and co-dominance (Ellegren, 2004).…”
Section: Introductionmentioning
confidence: 99%